Tantangan Hukum dan Keamanan Mobil Auto Pilot Perspektif Hukum Transportasi di Indonesia - Devid, Rahmad Ikbal; Syirva, Atika Nailah; Mas’udi, Salma Mawaddah (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The development of auto-pilot car technology as part of the modern transportation revolution presents various legal and security challenges, especially in the context of its implementation in Indonesia. This article aims to analyze the legal challenges that arise from the implementation of auto-pilot cars from a transportation law perspective in Indonesia, including the issue of legal responsibility in accidents. In addition, this article also evaluates the potential security risks associated with the use of autopilot technology, such as system errors and driver negligence. Normative juridical methods were used for this research, and focused on good legal standards found in Law of the Republic of Indonesia no. 8 of 1999 concerning Consumer Protection and Law of the Republic of Indonesia no. 22 of 2009 which regulates road traffic and transportation. The research results show that the current legal framework is not fully able to accommodate the operation of auto-pilot cars, especially in terms of legal responsibility in the event of an accident.